Two novel approaches to study arthropod anatomy by using dualbeam FIB/SEM. (March 2018) - Di Giulio, Andrea; Muzzi, Maurizio
Graphical abstract: Highlights: FIB/SEM can be used to replace TEM for anatomical and ultrastructural studies. FIB/SEM slicing allows overcoming many of the technical pitfalls of TEM preparations. FIB/SEM allows obtaining a serial sectioning of sample usable for 3D reconstruction. External morphology and internal anatomy can be analysed for the same microstructure. Outside-In method allows targeting individual microstructures prior to sectioning. Abstract: Transmission Electron Microscopy (TEM) has always been the conventional method to study arthropod ultrastructure, while the use of Scanning Electron Microscopy (SEM) was mainly devoted to the examination of the external cuticular structures by secondary electrons. The new generation field emission SEMs are capable to generate images at sub-cellular level, comparable to TEM images employing backscattered electrons. The potential of this kind of acquisition becomes very powerful in the dual beam FIB/SEM where the SEM column is combined with a Focused Ion Beam (FIB) column. FIB uses ions as a nano-scalpel to slice samples fixed and embedded in resin, replacing traditional ultramicrotomy. We here present two novel methods, which optimize the use of FIB/SEM for studying arthropod anatomy.